Influence of Alkaline and Acidic Co-precipitation Media on Fe₃O₄/TiO₂ Photocatalyst Performance for the Photodegradation of Cypermethrin - Nengsih, Sri; Rahman, Arief; Nur, Suardi (POSITRON, 2025)
The persistence of pesticide residues such as cypermethrin in water bodies has raised environmental concerns, necessitating the development of effective photocatalytic materials for their degradation. This study examines the influence of solvent-assisted magnetite synthesis on the structural, magnetic, and photocatalytic properties of Fe₃O₄/TiO₂ composites for cypermethrin degradation under UV light with a focus on a comparative approach between alkaline and acidic synthesis routes, which has not been extensively reported. Fe₃O₄ was synthesized via co-precipitation using NaOH and HCl to assess the impact of solvent conditions. Xray diffraction confirmed the spinel-phase structure in both samples, while SEM showed finer and more uniform particles in the NaOH-derived sample. VSM analysis revealed that Fe₃O₄–HCl exhibited higher saturation magnetization (Ms = 57.98 emu/g) but lower coercivity (Hc = 0.0206 T) than Fe₃O₄–NaOH (Ms = 41.26 emu/g; Hc = 0.0241 T), indicating synthesis-dependent magnetic properties. UV–Vis analysis identified a cypermethrin absorption peak at 220 nm, which was used to monitor degradation. The Fe₃O₄–NaOH:TiO₂ composite showed superior photocatalytic activity (31.98% degradation in 90 minutes) compared to Fe₃O₄– HCl:TiO₂ (22.86%). Kinetic modeling using the pseudo first-order equation yielded a higher rate constant for Fe₃O₄-NaOH:TiO₂ (k = 0.00172 min⁻¹; R² = 0.769), while Fe₃O₄–HCl:TiO₂ showed slower kinetics but better linearity (k = 0.00030 min⁻¹; R² = 0.9999). These results suggest that alkaline synthesis enhances particle morphology and charge transfer efficiency, improving photocatalytic performance. Therefore, Fe₃O₄–NaOH:TiO₂ represents a promising candidate for cypermethrin remediation in wastewater treatment.